Overexpression of a Brix Domain-Containing Ribosome Biogenesis Factor ARPF2 and its Interactor ARRS1 Causes Morphological Changes and Lifespan Extension in Arabidopsis thaliana - Maekawa, Shugo; Ueda, Yoshiaki; Yanagisawa, Shuichi (Frontiers in Plant Science, 2018)
The Brix domain is a conserved domain in several proteins involved in ribosome biogenesis in yeast and animals. In the Arabidopsis genome, six Brix domain-containing proteins are encoded; however, their molecular functions have not been fully characterized, as yet. Here we report the functional analysis of a Brix domain-containing protein, ARPF2, which is homologous to yeast Rpf2 that plays an essential role in ribosome biogenesis as a component of the 5S ribonucleoprotein particle. By phenotypic characterization of arpf2 mutants, histochemical GUS staining, and analysis using green fluorescence protein, we show that ARPF2 is an essential and ubiquitously expressed gene encoding a nucleolar protein. Co-immunoprecipitation and split-GFP-based bimolecular fluorescence complementation assays revealed that ARPF2 interacts with a protein named ARRS1, which is homologous to yeast Rrs1 that forms a complex with Rpf2 in yeast. Furthermore, the result of RNA immunoprecipitation assay indicated that ARPF2 interacts with 5S ribosomal RNA (rRNA) or the precursor of 5S rRNA, as well as with the internal transcribed spacer 2 in the precursors of 25S rRNA. Most intriguingly, we found that the overexpression of ARPF2 and ARRS1 leads to characteristic phenotypes, including short stem, abnormal leaf morphology, and long lifespan, in Arabidopsis. These results suggest that the function of Brix domain-containing ARPF2 protein in ribosome biogenesis is intimately associated with the growth and development in plants.